The Effect of Infant Massage and Breast Care on the Frequency and Breastfeeding Duration of Baby at Puskesmas Siak Hulu II - Komaria Susanti; Dewi Nopita Sari (Science Midwifery, 2021)
The problem of growth disorders for children under five in Indonesia has started to emerge from an early age between the ages of 1- 6 months so that efforts are needed to reduce the speed of growth disorders and to increase the percentage of weight gain. The aim of this study was to determine the effect of infant massage and breast care on the frequency and breastfeeding duration at Puskesmas Siak Hulu II. The type of research is quantitative with a pre-experimental design with one group pretest-posttest. The research was conducted in December 2019 to August 2020. The population was infants aged 0-6 months and 12 babies obtained by using purposive sampling. The research instrument was an observation sheet. Data collection using primary and secondary data, with data analysis using univariate and bivariate. The univariate results showed that the frequency and breastfeeding duration of for infants before massage was mostly adequate (83.4%), with an average frequency and breastfeeding duration of before massage was 9.58 and after massage and breast care was sufficient as much as 100%, the average frequency and the breastfeeding duration of in infants after massage was 12,17. The results of the Paired T test statistical test showed a p-value of 0.002 (α = 0.05). It is hoped that the Siak Hulu II Puskesmas can increase public knowledge and services, especially baby massage and breast care to increase the frequency and breastfeeding duration for babies.